2017
DOI: 10.1128/mbio.01872-17
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with RecombinantCryptococcusProteins in Glucan Particles Protects Mice against Cryptococcosis in a Manner Dependent upon Mouse Strain and Cryptococcal Species

Abstract: Development of a vaccine to protect against cryptococcosis is a priority given the enormous global burden of disease in at-risk individuals. Using glucan particles (GPs) as a delivery system, we previously demonstrated that mice vaccinated with crude Cryptococcus-derived alkaline extracts were protected against lethal challenge with Cryptococcus neoformans and Cryptococcus gattii. The goal of the present study was to identify protective protein antigens that could be used in a subunit vaccine. Using biased and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(124 citation statements)
references
References 51 publications
1
114
1
1
Order By: Relevance
“…Vaccination with glucan particles loaded with calnexin peptide was capable of eliciting protective immunity against both B. dermatitidis and Coccidioides posadasii experimental pulmonary infection, demonstrating the potential for vaccination strategies promoting calnexin‐specific T‐cell responses to protect against multiple endemic fungal infections. Various strategies, including recombinant proteins in glucan particles, engineered attenuated strains and alkaline extracts have shown promise in vaccination against experimental murine Cryptococcus infections …”
Section: Applications For Antifungal T Cellsmentioning
confidence: 99%
“…Vaccination with glucan particles loaded with calnexin peptide was capable of eliciting protective immunity against both B. dermatitidis and Coccidioides posadasii experimental pulmonary infection, demonstrating the potential for vaccination strategies promoting calnexin‐specific T‐cell responses to protect against multiple endemic fungal infections. Various strategies, including recombinant proteins in glucan particles, engineered attenuated strains and alkaline extracts have shown promise in vaccination against experimental murine Cryptococcus infections …”
Section: Applications For Antifungal T Cellsmentioning
confidence: 99%
“…Recently, a research group used a vaccination strategy to control cryptococcosis using glucan particles as a delivery system to carry protective protein antigens from C. neoformans or C. gattii . This approach induced CD4 + T-cell responses in the lungs of vaccinated mice, providing partial protection after challenge with C. neoformans or C. gattii [35]. These studies demonstrated that polarization of adaptive immune cells is critical to an appropriate immune response against cryptococcosis.…”
Section: Discussionmentioning
confidence: 99%
“…[59][60][61][62][63][64] More recently, the following strains have been constructed using the gene-targeting approach and used for immunization: C. neoformans interferon-γ (IFN-γ)expressing strain (H99γ); ZNF2 overexpression strain; ∆sgl1 strain; ∆cda1/2/3 strain; ∆cap59 strain; and C. gattii ∆cap60 strain. 14,53,[65][66][67][68] Interestingly, all groups immunized with C. neoformans recombinants had significantly improved survival rates when challenged with highly virulent C. gattii as well as with C. neoformans. Thus, it appears that these immunizations are cross-reactive to C. neoformans and C. gattii infection.…”
Section: Mannoproteinsmentioning
confidence: 96%
“…49,50) Both crude and single recombinant MPs have been used as vaccine antigens, and it was found that those vaccines significantly improved survival rates and decreased fungal burdens when challenged with C. neoformans and highly virulent C. gattii. 21,[51][52][53][54][55][56] C. neoformans culture filtrate antigen (CneF) is a crude antigen containing GXM, GalXM, and MPs, and MPs can be enriched from the culture filtrate via concanavalin A (ConA) affinity columns. 21,57) The following MPs have been identified as protective vaccine antigens: chitin deacetylase (Cda1, Cda2, also known as MP98 and Cda3); and a 25-kDa chitin deacetylase homologue (d25).…”
Section: Mannoproteinsmentioning
confidence: 99%
See 1 more Smart Citation